2005
DOI: 10.1590/s0034-72992005000400023
|View full text |Cite
|
Sign up to set email alerts
|

Algumas considerações sobre colesteatomas adquiridos pediátricos e adultos

Abstract: Authors debate about cholesteatomas, from the first time this word was employed, by Muller, in 1838, until the recent updates. They dissert about its definition, etiology and pathology and present basic concepts about its biology. They also make a wide review about pediatric cholesteathoma, its epidemiology and biology, and compare it with adult cholesteatoma. Finally, they describe some articles about ossicle chain erosion and its correlation with cholesteatoma perimatrix, collagen and collagenase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…There is no consensus in the literature regarding the influence of the type of cholesteatoma on hearing loss, or concerning the frequencies most affected. 11 , 13 , 14 , 15 , 16 , 17…”
Section: Introductionmentioning
confidence: 99%
“…There is no consensus in the literature regarding the influence of the type of cholesteatoma on hearing loss, or concerning the frequencies most affected. 11 , 13 , 14 , 15 , 16 , 17…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, facial paralysis might be caused by erosion of the facial canal and disturbances of the equilibrium organ due to detraction of the semicircular fistulas. Fortified inflammation causes mastoiditis, meningitis, intracranial abscesses, and sinus vein thrombosis [1][2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…4,11,12 Consensus opinion correlating the influence of the type of cholesteatoma on hearing loss or concerning the frequencies most affected is not available in literature. 11,13,14,15,16,17 Most studies have shown that there is an association between ossicular chain erosion and magnitude of hearing loss and that the most affected ossicle is the incus. 12,15,17 AIM: To evaluate the hearing loss in all types of cholesteatoma patients and analyse the association between nature of hearing loss and the type of cholesteatoma.…”
Section: Introductionmentioning
confidence: 99%